PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEAD TOGETHER (NHT) DISERTAI PERMAINAN SUCKER BALL TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 4 LEMBAH GUMANTI - doli, Misfar; Aima, Zulfitri; Lovia, Lita (Pendidikan Matematika, 2014)
ABSTRACTThe background reason of this research is the understanding of mathematical concept that still low among the 8th grade students of SMPN 4 Lembah Gumanti.Â  The aim of this research is to know whether the understanding of the mathematical concept will be better if cooperative learning method NHT and Sucker Ball game is applied rather that the concept given in conventional way to the 8th grade students of SMPN 4 Lembah Gumanti. The type of this research is experimental research, with random research design to subject. The instrument used for this research is the mathematical concept test and the student activity observation sheet. Data analysis was done by using Mann-Whitney test. Based on the result analysis. , its given that the Zhitung= -2,995 which is smaller than Ztabel, then the hypothesis if the research is acceptable. So it is concluded that the understanding of the mathematical concept of the student will be better by using the cooperative learning method NHT and Sucker Ball game rather than the conventional way of 8th grade students of SMPN 4 Lembah Gumanti.